Predictors of symptoms of posttraumatic stress and depression in family members after patient death in the ICU - Gries, Cynthia J; Engelberg, Ruth A; Kross, Erin K; Zatzick, Doug; Nielsen, Elizabeth L; Downey, Lois; Curtis, J Randall (Chest, 2010)
Patients' deaths in the ICU have been associated with a high burden of psychologic symptoms in families. This study identifies characteristics associated with psychologic symptoms in family members. Families of patients dying in the ICU or within 30 h of ICU discharge in 11 hospitals previously participated in a randomized trial. In the current study, we assessed these families for symptoms of posttraumatic stress disorder (PTSD) and depression with follow-up surveys. Outcomes included validated measures of PTSD (PTSD Checklist) and depressive (Patient Health Questionnaire) symptoms. Predictors included family member mental-health history, involvement in decision making, and demographics. Surveys were completed by 226 families. Response rate was 46% in the original randomized trial and 82% in this study. Prevalence (95% CI) of PTSD and depressive symptoms were 14.0% (9.7%-19.3%) and 18.4% (13.5%-24.1%), respectively. Family characteristics associated with increased symptoms included: female gender (PTSD, P = .020; depression, P = .005), knowing the patient for a shorter duration (PTSD, P = .003; depression, P = .040), and discordance between family members' preferences for decision making and their actual decision-making roles (PTSD, P = .005; depression, P = .049). Depressive symptoms were also associated with lower educational level (P = .002). Families with psychologic symptoms were more likely to report that access to a counselor (PTSD, P < .001; depression, P = .003) and information about spiritual services might have been helpful while the patient was in the ICU (PTSD, P = .024; depression, P = .029). Families demonstrated a high prevalence of psychologic symptoms after a death in the ICU. Characteristics associated with symptoms may help target interventions to reduce these symptoms. clinicaltrials.gov; Identifier: NCT00685893.